Pharmaceuticals as emerging pollutants: Implications for water resource management in Malaysia - Asvinidevi Arumugam; Khai Ern Lee; Pei Yuen Ng; Aida Soraya Shamsuddin; Aziemah Zulkifli; Thian Lai Goh (Emerging Contaminants)
The escalating contamination of water bodies with pharmaceuticals has raised global concerns due to potential health repercussions. This review aims to provide comprehensive insights into the occurrence of pharmaceuticals in Malaysian water bodies. Following PRISMA-ScR guidelines, a scoping review of studies from 2007 to 2024 was conducted using the Scopus, Web of Science and Google Scholar databases. Forty articles were included, reporting on pharmaceutical compounds in various water matrices. Analysis revealed 65 active pharmaceutical compounds spanning major therapeutic classes such as NSAIDs, antidiabetics, antihypertensives, antibacterials and natural and synthetic estrogens. Surface water was the most frequently studied matrix (n = 23), followed by sewage treatment plant effluent (n = 10), tap water (n = 11) and surface sediment (n = 7). Geographically, Selangor state accounted for the majority of studies (n = 29), with limited research in other states, reflecting a notable gap in national monitoring efforts. One of the main contributors to pharmaceutical occurrence in water bodies is household disposal. Despite the higher concentration of pharmaceutical residues in influent and effluent discharges compared to surface water, it is worth highlighting the removal capacity of wastewater treatment plants and the effectiveness of remediation processes. Despite these findings, research on pharmaceutical residues remains limited, with only seven out of Malaysia's 14 states investigated. This lack of comprehensive data underscores the urgent need for nationwide monitoring programmes and the integration of pharmaceutical pollution within national water quality standards. Given the environmental and public health implications, addressing this emerging pollutant issue necessitates a multifaceted approach to mitigate human exposure, safeguard water quality and ensure the sustainable management of water resources.